Microstructure and mechanical properties of BN-Si3N4 and AlON joints brazed with Ag-Cu-Ti filler alloy. Issue 4 (April 2018) - Liu, Mingxu; Liu, C.F.; Zhang, J.; Tao, Rui; Zhang, Qiang; Qi, Qin
Abstract: AlON was successfully brazed to BN-Si3 N4 using a Ag-Cu-Ti filler alloy. SEM, TEM and XRD studies revealed that a TiN + TiB2  + Ti5 Si3 reaction layer formed adjacent to the BN-Si3 N4 while a (Cu, Al)3 Ti3 O layer formed adjacent to the AlON. In addition, Ag-Cu eutectic, Cu(s, s) and AlCu2 Ti were observed in the brazing filler. The effect of brazing temperature on the microstructure and mechanical properties of the joints was investigated. As the brazing temperature increased, the reaction layers became thicker, while the thickness of the brazing seam decreased. Meanwhile, the amount and the size of AlCu2 Ti intermetallic compounds decreased. The shear strength of the joints first increased and then dropped with increasing the brazing temperature. A joint with a maximum strength of 94 MPa was obtained when it was brazed at 850 °C for 15 min.